355. Variability in the Current Evaluation and Management of Pediatric Encephalitis: Survey Results from an Emerging Infections Network Survey. (31st December 2020) - Dehority, Walter; Janowski, Andrew B; Messacar, Kevin; Messacar, Kevin; Polgreen, Philip M; Beekmann, Susan E
Abstract: Background: Childhood encephalitis causes severe morbidity and mortality. Difficulty identifying causative organisms and a lack of effective therapies leads to variability in management. The recent emergence of novel diagnostic tools and the increased recognition of auto-immune encephalitides has the potential to change the approach to this disease. Our objective was to assess the current evaluation and management of childhood encephalitis. Methods: An 11-question confidential, web-based survey was distributed by the Emerging Infections Network (EIN) of the Infectious Disease Society of America to 370 Pediatric Infectious Disease (ID) physicians between January 29 th and February 17 th, 2020. Respondents were characterized by practice region, experience since fellowship, place of employment and primary hospital type. Responses were analyzed with SAS, v 9.4. Results: Responses were obtained from 222 of 370 members (60%) (Table). Of the 222 respondents, 196 (88%) reported caring for children with suspected encephalitis and form the basis for this report. Multi-plex PCR testing of cerebrospinal fluid (CSF) in the initial evaluation of most children with suspected encephalitis was reported by 56% (with 65% of these respondents reporting the use of pathogen-specific confirmatory testing). CSF metagenomic next generation sequencing (mNGS) had been used by 47%, with 74% of all respondents stating they would use this test if likely diagnoses were excluded via standard testing (and 64% of these only using the test if the child was not improving). Variability in the interpretation of negative CSF mNGS results was reported (Fig 1a). Primary involvement of ID physicians in the diagnostic evaluation of auto-immune encephalitis was reported by 33%, yet only 55% of ID physicians reported feeling comfortable diagnosing this condition. Marked variation existed regarding criteria for the use of immunomodulating agents (Fig 1b) and the need for testing for autochthonous tropical viruses in the U.S. (Fig 1c). Background of 222 Respondents to an Emerging Infections Network Survey Assessing the Evaluation and Management of Pediatric Encephalitis. ID=Infectious Disease; VA=Veterans Affairs; DOD=Department of Defense *Respondents were significantly more likely than non-respondents to have <5 years of ID experience (p=0.04). Figure 1 Approaches to the Interpretation of CSF mNGS Results, Use of Immunomodulating Agents and Testing for Autochthonous Tropical Viral Pathogens in Children with Encephalitis Conclusion: Variation exists in the evaluation and management of childhood encephalitis, including the application of new diagnostic modalities and management of autoimmune encephalitides. Updated standardized management guidelines may improve implementation of advances in this realm. Disclosures: All Authors : No reported disclosures